Investigating the Effect of Knowledge Management on the Success of using Customer Relationship Management based on the Mediating Role of Organizational Factors (Case Study: Municipality of Tehran, Region 22) - Mehdi Jafarian, Mohammad; Ghorbani, Rahim; Alaei, Susan (International Journal of Engineering and Technology, 2018)
The present research studies the effect of knowledge management on the success of customer relationship management by considering the effects of organizational factors as a mediating factor. The type of research is applied and the method is descriptive survey. The statistical population of the study is the managers and experts of the municipality of Tehran 22nd district, that 207 of them were studied in the form of a statistical sample. Data analysis was performed using single-variable linear regression and confirmatory factor analysis. The results showed that the variables of customer relationship management technology, customer orientation and knowledge management capabilities were significantly influenced by the success of customer relationship management. Also, the variables of customer relationship management experience and organizational factors have a significant effect on the success of customer relationship management.Â